PERSEPSI MASYARAKAT TERHADAP CLEAN GOVERNANCE DI PROVINSI GORONTALO - Fitroy Ishak (Universitas Muhammadiyah Gorontalo, 2015)
Realizing good governance is not only a public expectations but also the demands of contemporary governance. This study aims to determine the public perception of